2020
DOI: 10.1186/s12964-020-00551-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 impairs presynaptic plasticity by blocking vesicle release following chronic brain hypoperfusion

Abstract: Background: Chronic brain hypoperfusion (CBH) is closely related to Alzheimer's disease (AD) and vascular dementia (VaD). Meanwhile, synaptic pathology plays a prominent role in the initial stage of AD and VaD. However, whether and how CBH impairs presynaptic plasticity is currently unclear. Methods: In the present study, we performed a battery of techniques, including primary neuronal culture, patch clamp, stereotaxic injection of the lentiviral vectors, morris water maze (MWM), dual luciferase reporter assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…CCH is considered to be the preclinical stage of mild cognitive impairment (Du et al, 2017 ); and it has already been proved to participate in the β-amyloid deposition, tau phosphorylation, neuronal death, impairment of hippocampal pre-synaptic plasticity, and theta oscillation in rats (Ai et al, 2013 ; Sun et al, 2015 ; Liu et al, 2016 ; Chen et al, 2017 ; Li et al, 2019 ; Yan et al, 2020 ). However, as the largest cholinergic nucleus and the theta generator of brain, whether the function of MS could be impaired by CCH is still unelucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCH is considered to be the preclinical stage of mild cognitive impairment (Du et al, 2017 ); and it has already been proved to participate in the β-amyloid deposition, tau phosphorylation, neuronal death, impairment of hippocampal pre-synaptic plasticity, and theta oscillation in rats (Ai et al, 2013 ; Sun et al, 2015 ; Liu et al, 2016 ; Chen et al, 2017 ; Li et al, 2019 ; Yan et al, 2020 ). However, as the largest cholinergic nucleus and the theta generator of brain, whether the function of MS could be impaired by CCH is still unelucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Transient forebrain ischemia following occlusion of the vertebral and common carotid arteries was reported inducing glutamate excitotoxicity and free radical formation (Gottlieb et al, 2006 ), and the hippocampal fEPSPs of CA3-CA1 circuit were found to be damaged due to impaired glutamatergic vesicle trafficking and vesicle release in CCH rat model (Yan et al, 2020 ; Zhang et al, 2020 ). These results suggested that impaired glutamatergic function might be the common feature in both acute and chronic brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus‐mediated delivery of miR‐181c partially rescued cognitive impairment in rat CCH 108 . Direct knockdown of miR‐153 or overexpression of the antisense molecule (lenti‐AMO‐153) may be a new strategy for alleviating the synaptic pathology and cognitive decline of VaD 109,110 …”
Section: Micrornas and Vcidmentioning
confidence: 99%
“…Considering the critical role of miR‐195 in VCID, the complement of exogenous miR‐195 may be a potentially anti‐dementia approach. A recent report showed that miR‐153 is involved in the CCH‐impaired hippocampal glutamatergic synaptic vesicle trafficking by binding site in the 3′ untranslated region (3’UTR) of the SYN1, Snap25, Vamp2, Stx1a, and Syt1 genes, which may be a new drug target for prevention or treatment of AD and VaD 109,110 …”
Section: Micrornas and Vcidmentioning
confidence: 99%